2008
DOI: 10.1002/adma.200800808
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Ionic Liquids Polymer for Naked‐Eye Detection of Anions

Abstract: A new concept for anion detection in a handy, rapid, and sensitive way is described based on the combination of the unique properties of both ILs and photonic crystals. By simple counteranion exchanging of the pendant IL units, the 3D highly ordered IL porous structure can directly sense different anions and easily convert the anion detection events into readable optical signals with color changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
93
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 29 publications
3
93
0
3
Order By: Relevance
“…The colorimetric response of CBPM sensors based on soft stimuli-responsive materials can originate from changes in both the periodicity and the refractive indices of its constituents, as shown in Figure 17C. Examples of soft materials used for CBPM sensors include hydrogels, 178 [287][288][289] and metal-organic frameworks. 290,291 Stimuli-induced shifts in the periodicity of these types of CBPM sensors can be induced by swelling or deformation that in turn results in the shift in the photonic stopband ( Figure 16B,i) and can be detected visually or using a spectrometer.…”
Section: Factors Influencing Sensing Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The colorimetric response of CBPM sensors based on soft stimuli-responsive materials can originate from changes in both the periodicity and the refractive indices of its constituents, as shown in Figure 17C. Examples of soft materials used for CBPM sensors include hydrogels, 178 [287][288][289] and metal-organic frameworks. 290,291 Stimuli-induced shifts in the periodicity of these types of CBPM sensors can be induced by swelling or deformation that in turn results in the shift in the photonic stopband ( Figure 16B,i) and can be detected visually or using a spectrometer.…”
Section: Factors Influencing Sensing Applicationsmentioning
confidence: 99%
“…In addition to multiple analyte sensing, hierarchy can be achieved using superparticles, which have been used as dispersible indicators for various stimuli. For example, spherical inverse opal superparticles based on poly(ionic liquids) were used for recognition of various ions and solvents, 288,289 and protein-modified silica superparticles were used as coding carriers in multiplex immunoassays. 325 Additionally, the high surface area of the pores can be used for adsorption and triggered release of drugs in addition to sensing.…”
Section: Factors Influencing Sensing Applicationsmentioning
confidence: 99%
“…Hu developed a kind of photonic ionic liquids polymer for naked-eye detection of anions by combination of the unique properties of both ionic liquids (IL) and photonic crystals. [73] It is shown that the prepared photonic IL film exhibits different reflection wavelength shifts upon soaking in various aqueous anion solutions. The induced color changes of the photonic ionic liquid film upon soaking in different anions aqueous solutions was shown in Figure 5.…”
Section: Photonic Crystalsmentioning
confidence: 99%
“…清华大学李广涛教授团队设计制备了多种类型的 响应性光子晶体用于多底物识别. 他们以二氧化硅粒子 自组装光子晶体膜为模板, 注入咪唑鎓盐离子液体单 体、交联剂和引发剂后, 通过紫外光照引起聚合, 再用 氢氟酸将二氧化硅粒子刻蚀, 制成聚离子液体的反蛋白 石光子晶体膜 [59] . 聚离子液体在含有阴离子的溶液中, 发生对阴离子的交换, 引起光子晶体溶胀或收缩, 造成 光子禁带发生移动.…”
unclassified